2018
DOI: 10.1007/s13744-018-0588-5
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Collard Green Genotypes to Bemisia tabaci Biotype B: Characterization of Antixenosis

Abstract: Bemisia tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) is an important pest of vegetable crops, including collard greens Brassica oleracea var. acephala (Brassicaceae). The use of resistant genotypes is an interesting option to reduce insect populations and can be used as an important tool for integrated pest management (IPM). This study evaluated 32 genotypes of collard greens against the attack of silver leaf whitefly, with the aim to characterize antixenosis. Initially, a multiple-choice trial was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In a study evaluating cucumber genotypes, Novaes et al (2020) found no signi cant correlation between this parameter and the presence of adults of B. tabaci MEAM1. Similarly, in a preference study with different genotypes of cabbage and the same white y species, no signi cant in uence of luminosity on the insect selection behavior was found (Domingos et al, 2018). It is likely, therefore, that in studies in which genotypes of the same plant species are evaluated, smaller variations in the luminosity of the plant tissue should be observed in relation to studies involving different plant species, as is the present case.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In a study evaluating cucumber genotypes, Novaes et al (2020) found no signi cant correlation between this parameter and the presence of adults of B. tabaci MEAM1. Similarly, in a preference study with different genotypes of cabbage and the same white y species, no signi cant in uence of luminosity on the insect selection behavior was found (Domingos et al, 2018). It is likely, therefore, that in studies in which genotypes of the same plant species are evaluated, smaller variations in the luminosity of the plant tissue should be observed in relation to studies involving different plant species, as is the present case.…”
Section: Discussionsupporting
confidence: 55%
“…The preference for infestation and oviposition by adults of B. tabaci MEAM1 in the described plant species was evaluated through free-choice assays, as described in previous studies (Domingos et al, 2018;Santos et al, 2021). For that, one plant of each plant species was sowed and cultivated in pots (1 L) containing Carolina Soil ® substrate and kept in a greenhouse free from insect infestation.…”
Section: Adult Attractiveness and Oviposition Testmentioning
confidence: 99%
“…Resistance against B. tabaci and associated viruses was also detected in many additional cultivated vegetable crops, such as watermelon [143,194], mung bean (Vigna radiata L.) [195,196], chili pepper [197][198][199], pepper accessions (Capsicum annuum L., C. chinense Jacq., and C. baccatum L.) [200], and collard (Brassica oleracea L. var. viridis) [201,202].…”
Section: Host-plant Resistancementioning
confidence: 99%
“…The accessions IAC-1544 (C. annuum), IAC-1545 (C. chinense), and IAC-1579 (C. annuum) could be classified as good sources of resistance against B. tabaci and associated virus Tomato severe rugose virus (ToSRV) for cultivated pepper [200]. Collard greens genotypes VE and J exhibited high resistance against B. tabaci [202].…”
Section: Host-plant Resistancementioning
confidence: 99%
“…Among the antixenotic factors in host plants against B. tabaci MEAM1, the type and density of trichomes play an important role and may influence the preference for feeding and/or oviposition (Oriani & Lara 2000, Oriani et al 2005, Oriani & Vendramim 2010. In addition, plant leaf color may be an important factor in the attractiveness of the whitefly (Prado et al 2015, Hasanuzzaman et al 2016, Domingos et al 2018, although these are characteristics that have not yet been studied. Some genotypes of P. vulgaris have already been evaluated for resistance to B. tabaci MEAM1, and some have been characterized as having antixenotic and/or antibiotic factors (Oriani et al 2005, Torres et al 2012, Peixoto & Boiça-Junior 2014, Silva et al 2014a.…”
Section: Introductionmentioning
confidence: 99%